2020
DOI: 10.1002/jgh3.12454
|View full text |Cite
|
Sign up to set email alerts
|

A case of juvenile eosinophilic cholangitis: Rapid peripheral blood hypereosinophilia after admission leading to diagnosis

Abstract: A 15‐year‐old boy was referred to our hospital with elevated hepatobiliary enzyme levels and jaundice. Magnetic resonance cholangiopancreatography performed at the previous medical facility revealed a stricture of the intrahepatic and extrahepatic bile duct. Computed tomography showed dilatation and wall thickness of the intrahepatic bile ducts. Primary sclerosing cholangitis or cholangiocarcinoma was suspected. Endoscopic retrograde cholangiopancreatography (ERCP) showed stricture in the intrahepatic and extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Matsumoto et al advocated that the EC bile duct image is reversible by treatment with CS (2), but bile duct stenosis often remains after treatment, as in the present case. Among individuals with EC, 30%-40% do not show eosinophilia (13)(14)(15). Our patient also showed no eosinophilia (eosinophil count >1,500/mm 3 ) for approximately 3 years of follow-up at our hospital and the previous hospital.…”
Section: Discussionmentioning
confidence: 49%
“…Matsumoto et al advocated that the EC bile duct image is reversible by treatment with CS (2), but bile duct stenosis often remains after treatment, as in the present case. Among individuals with EC, 30%-40% do not show eosinophilia (13)(14)(15). Our patient also showed no eosinophilia (eosinophil count >1,500/mm 3 ) for approximately 3 years of follow-up at our hospital and the previous hospital.…”
Section: Discussionmentioning
confidence: 49%
“…Furthermore, the number of infiltrating eosinophils in bile duct biopsies has not been well reported (only three cases), and the number of infiltrating eosinophils ranged from 4 to 60 per HPF. 8 Two biopsies were taken from the thickened bile duct wall in this case, and the eosinophil counts were greater than 50 and 200/HPF, respectively. There are no established criteria for eosinophil count in the histological diagnosis of EC.…”
Section: F I G U R Ementioning
confidence: 83%
“…6 Seow-En et al 7 proceeded with surgery for EC with bile duct stenosis, taking into consideration the exclusion of malignancy, recurrence with medical treatment, and side effects of steroid therapy, but it must be noted that EC is a benign disease and surgery is a highly invasive procedure. According to Fukatsu et al, 8 there are only seven reported cases of EC that were diagnosed by bile duct biopsy or cytology.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations